NDM‐producingEnterobacteriaceaein a Chinese hospital, 2014‐2015: identification of NDM‐producingCitrobacterwerkmaniiand acquisition ofblaNDM‐1‐carrying plasmidin vivoin a clinicalEscherichia coliisolate. Issue 11 (16th November 2016) - An, Jingna; Guo, Ling; Zhou, Lin; Ma, Yanning; Luo, Yanping; Tao, Chuanmin; Yang, Jiyong
Abstract : N/A: New Delhi metallo‐β‐lactamase (NDM)‐producing Enterobacteriaceae (NPE) shows prevalence in China. Little is known about the mechanisms related to the spread of NPE. Recently, a total of 51 non‐duplicated NPE isolates were collected from a tertiary‐care hospital in China and analysed for genetic relatedness by PFGE, antimicrobial susceptibility by Etest and sequence type by multilocus sequence typing. S1‐PFGE and Southern blot analysis or PCR amplification were used for plasmid profiling. Between 2014 and 2015, 22 Escherichia coli, 10 Klebsiella pneumoniae, 9 Enterobacter cloacae, 2 Enterobacter aerogenes, 3 Providencia rettgeri, 1 Klebsiella oxytoca, 1 Proteus mirabilis, 1 Citrobacter freundii, 1 Citrobacter werkmanii and 1 Raoultella planticola were identified as NPE. Results of PFGE and multilocus sequence typing showed that most strains were genetically unrelated. Among the 45 bla NDM ‐carrying plasmids, there were 25 IncX3 plasmids with a size of about 30 to 50 kb, one 100 kb IncX3 plasmid, 11 IncA/C plasmids with a size range from 70 to 300 kb, six 90 to 120 kb IncB/O plasmids, one IncN plasmid with a size of 100 kb and one 140 kb IncFrep plasmid. An NDM‐1‐producing isolate of C. werkmanii was identified, which had not been reported previously. An Escherichia coli strain was found acquiring a bla NDM‐1 ‐carrying IncFrep plasmid in vivo during infection. In conclusion, an NDM‐1‐producing isolate of C. werkmanii was identified. An Escherichia coli strain acquired a bla NDM‐1 ‐carrying plasmid in vivo . IncX3 and IncA/C plasmids with various sizes might have emerged as the main platforms mediating the spread of the bla NDM genes in China.